Integrating Good Waqf Governance and Visionary Leadership in Pesantren Waqf Management: Institutional Law as an Enabling Prerequisite - Hadiyanto Arif; Ifan Syafiuddin; Wahyudi Milbala Putra Panggar (Sinthop: Media Kajian Pendidikan, Agama, Sosial dan Budaya, 2026)
Waqf management in Indonesian pesantren faces persistent challenges related to institutional status, administrative capacity, accountability, leadership, and productive asset development. Existing studies generally examine Good Waqf Governance (GWG), leadership in Islamic educational institutions, and institutional law as separate domains, leaving their interaction insufficiently integrated in the context of pesantren-based waqf management. This study develops the Integrated Pesantren Waqf Governance Model (IPTGM) as a preliminary conceptual framework combining institutional law, GWG, and visionary leadership. A Systematic Literature Review guided by PRISMA 2020 was conducted using publications identified through Google Scholar, SINTA, Scopus, and supplementary reference searching. Of 124 initially identified records, 21 peer-reviewed articles published between 2016 and 2025 met the eligibility criteria and were included in the synthesis. The review was complemented by a focused normative analysis of Law No. 41 of 2004 on Waqf and Law No. 18 of 2019 on Pesantren. The findings indicate that institutional law provides an enabling regulatory environment but does not independently ensure effective governance. GWG contributes principles of transparency, accountability, responsibility, independence, and fairness, while visionary and values-based leadership may support institutional direction, organizational adaptation, professional capacity, and service-oriented accountability. The synthesis generates four propositions concerning institutional readiness, productive waqf management, leadership-supported GWG implementation, and multidimensional pesantren sustainability.